PERAN RELIGIOSITY DAN ATTITUDE DALAM INTENTION TO ADOPT ISLAMIC MICRO FINANCE IN YOGYAKARTA (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
This study was conducted to analyze member behavior in the Intention to Adopt Microfinance in Yogyakarta using the Theory of Planned Behavior (TPB) framework. The novelty of this study explains member behavior in the Intention to Adopt Microfinance based on the TPB, adding the element of Religiosity.This study used a quantitative approach with SEM to explain the relationship between exogenous and endogenous variables and mediating variables. The number of respondents used in this study was 120. The results show a direct relationship between Attitude and Intention to Adopt Sharia Microfinance, and a relationship between Religiosity and Attitude. An indirect relationship is evident, indicating that Religiosity influences Intention to Adopt Microfinance through Attitude. This study is limited to microfinance members in Yogyakarta, so the results cannot be generalized widely. This study can be used as a basis for policy-making for microfinance managers and as a reference for researchers examining the intention to adopt microfinance.
Keywords: Attitude; Religiosity; Micro Finance; Intention to Adopt; TPB